Welding - Geary, Don; Miller, Rex , 1929- (New York : McGraw-Hill, 2011)
A illustrated, step-by-step guide to oxyacetylene welding, metal cutting, soldering, and more
1. Oxyacetylene welding fuels -- 2. Oxyacetylene welding equipment -- 3. Setting up an oxyacetylene outfit -- 4. Other types of welding and equipment -- 5. Metals and their properties -- 6. Welding supplies -- 7. Soldering -- 8. Brazing and braze welding -- 9. Beginning welding -- 10. Welding thicker metals -- 11. Protection and problems -- 12. Weldability of certain metals -- 13. Cutting metal -- 14. Safety -- 15. Home workshop -- 16. Metal projects
Includes index
Keywords: Oxyacetylene welding and cutting